Terahertz radiation generation by laser interaction with a periodic array of GaAs structure - . Sandeep; Hitendra K. Malik (Results in Optics, 2023)
In the current study, a method for generating terahertz (THz) radiation using a GaAs structure array and an incident laser is proposed. When a laser beam is directed onto GaAs material, carriers are generated within the material. These carriers, under the influence of an electric field, produce a transient current as they respond to the applied field. The time-varying current is induced in short intervals of picoseconds. Consequently, this induced current functions as a dipole. The calculation of THz emission from a GaAs array involves the application of antenna theory to the photoconductive antenna. This calculation specifically considers the electron mobility constant as the sole factor during the rising of the current density. The phased array of oscillating dipoles is generating coherent terahertz (THz) radiation. The electrical current flowing along the length of these structures is accountable to produce terahertz (THz) radiation, where the entire system acts as phase-array dipole antennae. Laser interaction with a periodic array of GaAs structures has a wide range of applications across various domains, such as imaging, spectroscopy, communications, non-destructive testing, security, biomedical research, and material science.